Inglês em rede : crenças e motivação de aprendizes em um curso a distância - Perine, Cristiane Manzan (2013)
The present study is grounded on Applied Linguistics, which is understood as a science responsive to the contemporary social life (MOITA LOPES, 2006). It focuses on the characterization of affective-cognitive constructs, beliefs and motivation, and digital technology in language learning. This research was designed in order to investigate students beliefs about distant English learning and its connection with their motivation to learn. The theoretical framework is based on three themes: beliefs, motivation and digital technology. Beliefs are interpreted as ideas, opinions and assumptions that teachers and students have regarding language teaching and learning formed from their experience (BARCELOS, 2001). Motivation is conceived as something that leads us to initiate and sustain action (DÖRNYEI, 2005). Digital technology is considered to cause a reconfiguration on teachers´ and students traditional roles (PAIVA, 2005). Ten undergraduate students from different courses in a federal university in Minas Gerais took part in this study. They were enrolled in an elective course Inglês Instrumental a Distância I (IngRede). In this qualitative research study (BORTONI-RICARDO, 2008), the data were collected through a questionnaire, reflexive journals, a semi-estructured virtual interview and examination of students participation on Moodle. In the data analysis, it was useful the proposition of Gillham (2000) for content analysis allied to the WordSmith Tools software. Based on the data results, we suggest the arrangement of a network of beliefs about aspects of distance English learning, which connects beliefs about the English language, beliefs about computer use to learn English, beliefs about student s and teacher s roles. We also show that motivation to distance English learning is constituted by an initial motivation, motivation in course and retrospective motivation. Lastly, we point out how the relationship between beliefs and motivation in a virtual learning environment is framed by specificities of the digital context, in which students beliefs about distance English learning influence their motivation. They can favor or inhibit students motivation in this context.